2011
DOI: 10.1108/17473611111141614
|View full text |Cite
|
Sign up to set email alerts
|

An empirical assessment of the relationship between character/ethics education and consumer behavior at the tweens segment: the case of Egypt

Abstract: PurposeThe current study seeks to focus on highlighting the extent of changes in consumer behavior by character/ethics education. The research is designed as a pioneer empirical study, sampling Egypt as an example of a growing consumer market as well as an illustration of the relevance of character education programs for inducing changes in consumption patterns. The central aim of the work is to contribute to the body of knowledge of marketing science and marketing ethics with respect to strategic issues like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Although values above 0.7 are generally acceptable, it is preferable to have values over 0.8. This high level of reliability again confirms the questionnaire's construct validity (Hair et al ., 2006; El‐Bassiouny et al ., 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Although values above 0.7 are generally acceptable, it is preferable to have values over 0.8. This high level of reliability again confirms the questionnaire's construct validity (Hair et al ., 2006; El‐Bassiouny et al ., 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Because moral identity plays a key role in consumer ethics, and given that character traits are integral to moral identity, there is a need to examine the possible benefits of character development programs. Although some studies have questioned the effectiveness of such programs (Davis 2003), others have shown that character education for school children may have positive effects on subsequent consumer behavior (El-Bassiouny, Taher, and Abou-Aish 2011). The current study does not empirically test whether character education programs are effective, because this is beyond the scope of the research.…”
Section: Implications For Macromarketing and Public Policymentioning
confidence: 99%
“…Few studies found that Millennials are receptive to ethical issues (Bucic et al , 2012; Smith, 2011); others found they have higher level of narcissism (Twenge and Campbell, 2008) and are highly conscious about social, cultural, and environmental issues (Sheahan, 2005). In contrast, Millennials, especially in developing countries, can be receptive to unethical behavior, such as downloading copyrighted digital materials illegally, buying pirated goods and photocopying books illegally (Aleassa et al , 2011; El-Bassiouny et al , 2011; Tjiptono et al , 2016); are less ethical in general (VanMeter et al , 2013; World of Work Survey, 2008); and are more likely to engage in specific unethical behavior such as calling in sick when they are not (Ethics Resource Center, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%